Properties of a Membrane-bound Phosphatase from the Thylakoids of Spinach Chloroplasts - Mulligan, R. Michael (1980)
A 3-phosphoglycerate phosphatase activity of about 2 micromoles per minute per milligram chlorophyll is associated with the thylakoid membranes of spinach chloroplasts. The K(m) for 3-phosphoglycerate is 3 millimolar. The enzyme can be solubilized from thylakoid membranes by treatment with 0.33 molar MgCl(2) or sodium deoxycholate. The activity is not stimulated by sulfhydryl reagents or the addition of 10 millimolar MgCl(2). The enzymic activity is insensitive to ethylenediaminetetraacetate. The pH optimum is broad, between 5.5 to 7.5. Although the substrate specificity is broad, 3-phosphoglycerate is the best substrate of those tested at neutral pH. However, p-nitrophenyl phosphate was a more effective substrate at pH 5.5. The enzyme exhibits the general characteristics of an acid phosphatase.